THE ROLE OF DIGITAL TECHNOLOGIES IN AGRICULTURAL ORGANIZATIONS - Dosent., Karieva Gulnora Abdullayevna; Assistant., Normurodov Sarvar Norboy o‘g‘li (Scholar Express Journals, 2024)
This article discusses foreign experience in the introduction of digital technologies in the conduct of smart agriculture, as well as the need for the use of automated systems in agriculture
Keywords: Digital technologies; digitalization; livestock; consumers